DAMPAK PENGGUNAAN SMARTPHONE TERHADAP KEHIDUPAN SEKSUAL (STUDI KASUS AKSES PORNOGRAFI ONLINE DI KALANGAN MAHASISWI UNIVERSITAS RIAU) - Febry Kosdanita; Yusmar Yusuf (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
The purpose of this study was to determine the student sexual act after accessing pornography. The method used in this research is descriptive qualitative, where the informant obtained came from Riau University student with different departments and faculties. To determine informants pusposive researchers used a technique of sampling and data collection techniques by observation and interview. Smartphones and the Internet simply can not be separated, because of the Internet as an application support that is needed by the community. But in modern times the Internet is widely misused by the public, as well as the spread of pornography in the form of electronic information. Indonesia is a country that can not be separated from the issue of pornography, Indonesia was ranked second out of 10 largest countries in the world as accessor cyberporn. It is a major influence on sexual life. From observations and interviews can be seen that the sexual acts performed Riau University student after accessing pornography is that three of the seven informants imitate what they see.Keywords: Smartphone, Pornography, Sexual Acts.